2015
DOI: 10.12692/ijb/6.12.71-80
|View full text |Cite
|
Sign up to set email alerts
|

Marker-Assisted introgression of saltol locus into genetic background of brri dhan49

Abstract: The major purpose of this research was to introgress Saltol QTL into the genetic background of BRRI dhan49 through marker-assisted backcrossing. FL478 was used as a donor parent of Saltol QTL. Marker assisted backcrossing strategies were applied to develop BRRI dhan49-Saltol lines. A primer polymorphism survey was carried out between the two parental genotypes viz. BRRI dhan49 and FL478. A total of 363 SSR and InDel primers were surveyed and a total of 96 markers (27%) were found polymorphic. A cross was made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Flanking markers have been found to differ in their reliability and stability for specific QTLs: for example, RM8094 and RM 3412 were found reliable and diagnostic for Saltol, being more closely flanking than others markers like RM 493 (Islam et al 2012;Al-Amin et al 2013;Babu et al 2014). The successful utilization of MAS for salinity tolerance is illustrated by introgression of Saltol into several elite varieties of different countries like PB1121 and PB6 in India (Singh et al 2011), AS996 BT7, Bac Thom 7 and Q5BD in Vietnam (Huyen et al 2012(Huyen et al , 2013Linh et al 2012;Vu et al 2012;Luu et al 2012), BRRI dhan 49 in Bangladesh (Hoque et al 2015) and Novator in Russia (Usatov et al 2015). Singh et al 2016 reported the introgression of Saltol into seven popular varieties (ADT45, CR1009, Gayatri, MTU1010, PR114, Pusa 44 and Sarjoo 52) through a multi-institutional network project 'From QTL to variety: marker assisted breeding of abiotic stress tolerant rice varieties with major QTLs for drought, submergence and salt tolerance' a collaborative project of India and IRRI, Philippines.…”
Section: Marker-assisted Strategy For Introgression Of Salinity Tolerance In Rice and Rice Varieties For Salt-affected Soilsmentioning
confidence: 99%
“…Flanking markers have been found to differ in their reliability and stability for specific QTLs: for example, RM8094 and RM 3412 were found reliable and diagnostic for Saltol, being more closely flanking than others markers like RM 493 (Islam et al 2012;Al-Amin et al 2013;Babu et al 2014). The successful utilization of MAS for salinity tolerance is illustrated by introgression of Saltol into several elite varieties of different countries like PB1121 and PB6 in India (Singh et al 2011), AS996 BT7, Bac Thom 7 and Q5BD in Vietnam (Huyen et al 2012(Huyen et al , 2013Linh et al 2012;Vu et al 2012;Luu et al 2012), BRRI dhan 49 in Bangladesh (Hoque et al 2015) and Novator in Russia (Usatov et al 2015). Singh et al 2016 reported the introgression of Saltol into seven popular varieties (ADT45, CR1009, Gayatri, MTU1010, PR114, Pusa 44 and Sarjoo 52) through a multi-institutional network project 'From QTL to variety: marker assisted breeding of abiotic stress tolerant rice varieties with major QTLs for drought, submergence and salt tolerance' a collaborative project of India and IRRI, Philippines.…”
Section: Marker-assisted Strategy For Introgression Of Salinity Tolerance In Rice and Rice Varieties For Salt-affected Soilsmentioning
confidence: 99%
“…For example, low rainfall resulting in drought in the Mekong River Delta of Vietnam results in intrusion of saline sea-water to areas used for crop cultivation ( Larson, 2016 ), with about 1.8 million ha of the growing area subjected to increased dry-season salinity ( Smajgl et al., 2015 ). To address yield losses, progress on breeding for tolerance to individual abiotic stresses such as drought, salinity, and flooding has been significant, and several tolerant varieties suitable for specific stresses have been developed and made available for farmer cultivation ( Gregorio et al., 2013 ; Amaranatha et al., 2014 ; Hoque et al., 2015 ; Singh et al., 2016 ; Waziri et al., 2016 ; Dar et al., 2018 ). However, little progress on development of varieties tolerant to combined abiotic stresses has been reported.…”
Section: Introductionmentioning
confidence: 99%